Facilitating and hindering aspects of the work of nurses in hospital managerial positions - Nilce Mara da Silva; Vivian Aline Mininel; Silvia Helena Henriques; Ana Martha de Almeida Limongelli; Ana Paula Pereira; Lucieli Dias Pedreschi Chaves (Universidade Federal de Santa Maria, 2020)
Objective: To identify aspects that facilitate and hinder the work of nurses in managerial positions in a public teaching hospital. Method: A descriptive study with a qualitative approach, developed in a public, tertiary hospital, using the Critical Incident Technique. Sample consisting of 15 nurses in managerial positions for at least one year. Results: 42 situations were obtained, 66.6% being of negative references; 57 behaviors showing 84.2% of positive references and 74 consequences getting 58.1% of negative references. Conclusion: The aspects that facilitate the work of nurses in managerial positions are situations/behaviors/consequences related to team/patient/family interaction; work unit management; management group implementation and communication. In contrast, the hindering aspects are related to organizational structure, infrastructure management and people management.